Pengaruh Brand Personality dan Service Quality terhadap Repurchase Intention - Vinka Fitria Nuryani; Hendrati Dwi Mulyaningsih; Mochamad Malik Akbar Rohandi (Bandung Conference Series: Business and Management, 2024)
Abstract . This research focuses on the variables Brand Personality , Service Quality and Repurchase IntentionThis type of research is included in descriptive and verification research with quantitative methods. The sampling technique used in this research is nonprobability sampling, namely purposive sampling. The method used in this research is a survey method with a questionnaire instrument as the data collection technique. The object of research in this study is consumers who have purchased Janji Jiwa Coffee more than once who live in the city of Bandung with a total of 204 respondents. The results in this study show that Brand Personality does not have a positive and significant effect on Repurchase Intention and Service Quality is proven to partially have a positive and significant effect on Repurchase Intention. Then simultaneously Brand Personality and Service Quality have a positive effect on Repurchase Intentions. Abstrak. Penelitian ini berfokus kepada variabel Brand Personality , Service Quality dan Repurchase Intention. Jenis penelitian ini termasuk kedalam penelitian deskriptif dan verivikatif dengan metode kuantitatif. Tekhnik sampling yang digunakan pada penelitian ini adalah non probability sampling yaitu purposive sampling. Metode yang digunakan dalam penelitian ini adalah metode survey dengan instrumen kuesioner sebagai tekhnik pengumpulan datanya. Objek penelitian pada penelitian ini adalah konsumen yang sudah lebih dari 1x membeli Kopi Janji Jiwa yang berdomisili di kota Bandung dengan jumlah responden sebanyak 204 orang. Hasil dalam penelitian ini menunjukkan bahwa Brand Personality tidak berpengaruh positif dan signifikan terhadap Repurchase Intention dan Service Quality terbukti secara parsial berpengaruh positif dan signifikan terhadap Repurchase Intention. Kemuadian secara simultan Brand Personality dan sercive quality berpengaruh positif terhadap Repurchase Intention.